Requiem for a national ideal? Social solidarity, the crisis of French social security, and the role of global financial markets - Clark, G (Pion Ltd., 2001)
It is well appreciated that demographic trends threaten the integrity of continental European systems of social security. For France these trends imply a long-term financial crisis as well as a crisis of confidence in national economic and social institutions. The payment of social security entitlements is a recurrent and largely unresolved political issue; proposals for comprehensive reform are heavily contested, involving political interests willing to go to the streets. At the same time, governments' incremental changes in benefit formula and accounting have discounted the expected value of future retirement benefits. In this paper, I begin by sketching the logic of pay-as-you-go social security, identifying the basic economic principles and social institutions that sustain such systems. One goal of the paper is to articulate the economic and philosophical roots of social solidarity and the importance of the state as the custodian of the social contract between generations. In doing so, I sketch out the French ideal: a coherent social security system based upon self-reinforcing mutual obligations and institutions. A second goal of the paper is to show how and why the French social security system became unsustainable. Demographic trends have been exacerbated by the use of the retirement system as a form of labour-market compensation policy, thereby undercutting both its financial and its political legitimacy. The third goal of the paper is to indicate how and why global financial markets may play a significant role in resolving the crisis of social security. Basically, I dispute the argument that national systems of social security will persist into the future; internal inconsistencies and the possible defection of those not served by such institutions combined with external opportunities may overturn the past. By making this argument, I do not mean to suggest that the Anglo-American model is necessarily superior to social security systems based on social solidarity. Rather, my point is entirely argumentative: solemn incantations that defend the past, whatever their best intentions, may simply reinforce the nature and significance of the pending crisis.